DETERMINAN MINAT NASABAH MENABUNG DI BANK SYARIAH - Niken Probondani Astuti (AkMen JURNAL ILMIAH, 2019)
The study aims to know : (1) The effect of religiusitas on the interst of saving in Islamic bank, (2) The effect of service on the interst of saving in Islamic bank, (3) The effect of savings product on the interst of saving in Islamic bank. (4) The effect of profit sharing on the interst of saving in Islamic bank. As quantitative research, a survey method using a questionnaire was used. The sampling technique was accidental sampling. The population in this customer PT BNI Syariah Makassar .The sample was 90 respondents. Methods of data analysis using is descriptive analysis and multiple regression techniques. The results showed that religiusitas, service, savings product and profit sharing influenced positive and significant on the interst of saving in Islamic bank.